Respuesta :

Answer: x = -3, y = 2

Step-by-step explanation:

3x + 2y = -5   →   3(3x + 2y = -5)   →   9x + 6y = -15

4x - 3y = -18   →   2(4x - 3y = -18)   →   8x - 6y = -36

                                                            17x       = -51

                                                         ÷17           ÷17

                                                               x      =   -3

 3x + 2y = -5

3(-3) + 2y = -5

 -9  + 2y = -5

 +9           +9

         2y =   4

      ÷2      ÷2

           y =  2